TAFSIR TENTANG LAFAZ Al-UMMAH DALAM AL-QUR'AN - Zainuddin Zainuddin (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2016)
Among the commands of the Koran to Muslims is to become the people as the people of ideal. The concept of race is ideal from the perspective of the Koran is a thesis titles raised by researchers because it can be conditioned to the morals or behavior everyday at the present time. Can we note its many conflicts in the name of religion. And there is also a human being excessive in performing religious rituals, causing a fanaticism. While the Qur'an has told Muslims to be the ideal race mid race. Is meant here is the same as khayra people or race the best. Position itself in the middle, is not inclined to the world nor in the Hereafter. Muslims as the best race to be able to realize himself against all the people in this world. Ummah is mentioned in the Qur'an with the form lafadz people wasatan, khayra people, muqtasid people, and people wahidah. The characteristics of an ideal community in the perspective of the Koran that is faith in God, carrying out commanding the good and forbidding the evil, to be fair, it is no exaggeration in religion, and maintaining kinship.